2016
DOI: 10.1021/acs.biomac.6b01236
|View full text |Cite
|
Sign up to set email alerts
|

Polycationic Nanofibers for Nucleic Acid Scavenging

Abstract: Dying cells release nucleic acids (NA) and NA-containing complexes that activate inflammatory pathways of immune cells. Sustained activation of these pathways contributes to chronic inflammation frequently encountered in autoimmune and inflammatory diseases. In this study, grafting of cationic polymers onto a nanofibrous mesh enabled local scavenging of negatively charged pro-inflammatory molecules in the extracellular space. Nucleic acid scavenging nanofibers (NASFs) formed from poly(styrene-alt-maleic anhydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
1
7
0
1
Order By: Relevance
“…The ability of HDMBr to bind free plasma mtDNA could be a large part of its protective mechanism. This is also supported by recent studies in which NASPs were immobilized on microspheres or incorporated into a nanofiber mesh and co-incubated with cells and CpG DNA to produce cellular protection ( 62 , 63 ).…”
Section: Discussionsupporting
confidence: 67%
“…The ability of HDMBr to bind free plasma mtDNA could be a large part of its protective mechanism. This is also supported by recent studies in which NASPs were immobilized on microspheres or incorporated into a nanofiber mesh and co-incubated with cells and CpG DNA to produce cellular protection ( 62 , 63 ).…”
Section: Discussionsupporting
confidence: 67%
“…The following study further demonstrated that using these NA-binding polymers to limit NA-induced inflammation is effective in some inflammatory and autoimmune diseases ( 17 20 ). Considering the toxicity of cationic materials administered systemically, a local ( 31 ) or ex vivo method ( 32 ) using immobilized polycations to remove DAMP molecules may be a better choice for easy clinical translation.…”
Section: Discussionmentioning
confidence: 99%
“…Using these nucleic acid-binding polymers (NABP) to remove the DAMP molecules, we had demonstrated that the scavenging approach works in animal models of CpG-induced or RNA-induced acute liver injury 19 , thrombosis 29 , and SLE 20 , 30 . To reduce toxicity, we had immobilized the NABP on fibrous membrane to remove the DAMP molecules in a local 31 or ex vivo manner 32 . Motivated by the high NA-binding capacity of the immobilized configuration of NABP in these recent studies, we propose to use cNP as a DAMP scavenger, which has not been studied before, for RA treatment.…”
Section: Discussionmentioning
confidence: 99%